Analysis of the Effects of Economic Potential on Economic Growth of Deli Serdang Regency - Puguh Setiandono; H.B Tarmizi; Rujiman Rujiman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The objective of the research is to analyze economic potential, economic growth rate, and high-ranking sectors which prioritize the development in Deli Serdang Regency. The data are analyzed by using Location Quotient (LQ) analysis, Dynamic Location Quotient (DLQ) analysis, Shift Share analysis, and Klassen Typology. The result of LQ analysis shows that there are 5 (five) basic sectors: transportation and warehousing sector, processing industry sector, construction sector, accommodation and food and beverage supply sector, and electricity and gas supply sector. The result of DLQ analysis shows that there are 10 (ten) basic sectors in the future: processing industry sector, electricity and gas supply sector, wholesale and retail sector, automobile and motorcycle reparation sector, transportation and warehousing sector, accommodation and food and beverage supply sector, financial service and insurance sector, real estate sector, company service sector, education service sector, health service and social activity sector. The result of Shift Share analysis shows that there are 10 (ten) basic sectors which are competitive sector which has positive differential values: processing industry sector electricity and gas supply sector, construction sector, wholesale and retail sector, automobile and motorcycle reparation sector, accommodation and food and beverage supply sector, financial service and insurance sector, real estate sector, company service sector, education service sector, and health service and social activity sector. The result of Klassen Typology shows that there are 5 (five) prioritized sectors: processing industry sector, electricity and gas supply sector, construction sector, transportation and warehousing sector, and accommodation and food and beverage supply sector. Based on the four analyses above, it is concluded that the prioritized sectors are processing industry sector, electricity and gas supply sector, construction sector, and accommodation and food and beverage supply sector.